Development of maximum strength, resistance and body composition: a comparison between users and non-users of anabolic androgenic steroids - Cristiano Stechechen, Rodrigo; Gemin Vidal, Rafael (Brazilian Journal of Implantology and Health Sciences, 2023)
The present study aimed to verify the effects of the use of anabolic androgenic steroids (AAS) in the development of maximum strength, resistance strength and body composition in resistance training practitioners. This research is characterized as applied, with a descriptive field study with a quantitative approach. The intentional non-probabilistic sample was composed of 20 male individuals, experienced in strength training. Participants were allocated into two groups: GU (group of EAA users), and GNU (non-EAS users group). The subjects were submitted to an evaluation of body composition, maximum strength test (1RM) and maximum repetitions test (80%RM). The results found indicate that the use of EAA increases the production of maximum strength and relative strength, causing a moderate increase in fat-free mass. The improvement in performance by its use is not found in the number of maximum repetitions at 80% RM, as well as it does not seem to influence fat mass and body fat percentile.